Influence of silane coupling agent on the mechanical performance of flowable fibre-reinforced dental composites. Issue 7 (July 2022) - Thadathil Varghese, Jerrin; Cho, Kiho; Raju,; Farrar, Paul; Prentice, Leon; Prusty, B. Gangadhara
Abstract: Objectives: This experimental investigation explored the optimisation of silane treatment of surface-modified S-2 Glass fibres in restorative dental composites for improved mechanical performance. The influence of optimum amount of silane to improve the interfacial adhesion at the fibre-matrix interfaces and its effect on the mechanical properties of the restorative composites were explored. Methods: S-2 Glass fibres of 5 μm diameter and 250 μm length were surface modified using the acid etching technique. The etched fibres were then treated with either 3-methacryloxypropyltrimethoxysilane (3-MPS), 3-Glycidoxipropyltrimethoxysilane (3-GPS) or 8-methacryloxyoctyltrimethoxysilane (8-MOTS) at varying molar % / wt% concentrations. Fibres that were not silanised with any silane coupling agents were used as the control sample. The silanol content of each mixed silane was observed using Fourier transform infrared (FT-IR) spectroscopy analysis. Fibres (5 wt%) with optimised molar% / wt% silane coupling concentration were added to UDMA/TEGDMA dental resin. Mechanical properties such as flexural strength, flexural modulus, and the breaking energy of the materials were evaluated using a comprehensive experimental programme. Results: FTIR spectrum of glass fibre silanised with each silane coupling agent revealed many peaks from 3800 to 1400 cm −1, indicative of -CH3, -CH2, and CO bonding, suggesting the proper silanization of the fibre. The contact angle test revealed that optimum wt% concentration of 3-MPS, 3-GPS and 8-MOTS were 0.5%, 0.8% and 1.4% respectively. The flexural strength of the fibre-reinforced with optimum concentration of 3-MPS (DC-3-MPS_0.5%) increased by 7.0% compared to those of the 2 wt% concentration of 3-MPS fibre-reinforced composite (DC-3-MPS_2.0%). While the flexural strength of optimum concentration 8-MOTS grafted dental resin composites (DC-8-MOTS_1.4%) were 9.9% higher than that of 2 wt% concentration 8-MOTS grafted dental resin composite (DC-8-MOTS_2.0%) and the flexural strength of optimum concentration of 3-GPS (DC-3-GPS_0.8%) was 7.5% higher when compared to that of 2 wt% concentration 3-GPS grafted dental resin composites (DC-3-GPS_2.0%). A concurrent trend was found while investigating the fracture behaviour of the dental composite with optimum wt% concentration of each silane coupling agent against its corresponding higher wt% concentrations. The ANOVA results showed that the optimum fibre-reinforced dental composites grafted with 8-MOTS showed better mechanical behaviour when compared to 3-GPS and 3-MPS. Significance: The interfacial adhesion between the fibre and the resin due to silane coupling agents has helped to improve the mechanical properties of the fibre-reinforced dental composite. This is the first experimental study to provide a thorough investigation into the significance of the optimal use of silane coupling agents to treat the S-2 Glass fibres and subsequently the influence on the mechanical performance of the fibre-reinforced flowable dental composites. Graphical Abstract: ga1 Highlights: Relationship between hydrophobicity/hydrophilicity of the S-2 Glass fibre to the Silane Coupling Agent was investigated . Importance of optimum concentration of SCA to achieve maximum adhesion at the fibre-matrix interface was assessed . Effect of surface modification of S-2 Glass fibre with different SCAs in fibre-reinforced dental composite was studied . The effect of hydrogen bonding between SCA and glass fibre on the mechanical properties of the composites were examined .